The abbreviated larval development of Ozius guttatus H. Milne Edwards, 1834 (Crustacea: Brachyura: Eriphioidea: Oziidae) - Clark, Paul F.; Ng, Peter K. L. (Zootaxa, 2025)
Ovigerous Singapore specimens of Ozius guttatus H. Milne Edwards, 1834 (Eriphioidea: Oziidae) were collected and their larvae reared in the laboratory with an expectation that this species would have a similar larval development to O. truncatus H. Milne Edwards, 1834 and O. rugulosus Stimpson, 1858, e.g., four zoeal stages before the moult to megalop. This, however, was not the case, in fact O. guttatus has an abbreviated development with only two zoeal stages before the metamorphosis to megalop. The purpose of this present study is to describe the larval development of O. guttatus and compare its abbreviated zoeal development with the descriptions of Wear (1968) and Kakati & Nayak (1977) for O. truncatus and O. rugulosus, respectively. Many zoeal characters of O. guttatus are expressed early and the significance of these are discussed. In addition, the zoeal development of O. guttatus is compare with two zoeal stages of Pilumnus sluiteri De Man, 1842 (Pilumnoidea: Pilumnidae) as described by Clark & Ng (2004).